A Revision of Freud's Theory of the Biological Origin of the Oedipus Complex. (20th December 2021) - Solms, Mark
Abstract : This revision concerns primarily the biological origin of the Oedipus complex, classically understood as an inherited primal phantasy . However, a reconceptualization of the origin of what Freud called the nuclear complex of the neuroses also has consequences for understanding its nature. A review of current knowledge relevant to the biological mechanisms of inheritance and the type of memory system that Freud had in mind, and a review of modern instinct theory, suggests that the Oedipus complex is not an innate predisposition but rather the almost inevitable outcome of a combination of simpler biological processes.